알렌 마우스 브레인 아틀라스를 이용한 반자동 신경섬유지도 분석 : 여기수와 신호대잡음비간의 DTI 획득 비교 - 임상진; 백현만; Im, Sang-Jin; Baek, Hyeon-Man (한국방사선학회 논문지, 2020)
Advancements in segmentation methodology has made automatic segmentation of brain structures using structural images accurate and consistent. One method of automatic segmentation, which involves registering atlas information from template space to subject space, requires a high quality atlas with accurate boundaries for consistent segmentation. The Allen Mouse Brain Atlas, which has been widely accepted as a high quality reference of the mouse brain, has been used in various segmentations and can provide accurate coordinates and boundaries of mouse brain structures for tractography. Through probabilistic tractography, diffusion tensor images can be used to map comprehensive neuronal network of white matter pathways of the brain. Comparisons between neural networks of mouse and human brains showed that various clinical tests on mouse models were able to simulate disease pathology of human brains, increasing the importance of clinical mouse brain studies. However, differences between brain size of human and mouse brain has made it difficult to achieve the necessary image quality for analysis and the conditions for sufficient image quality such as a long scan time makes using live samples unrealistic. In order to secure a mouse brain image with a sufficient scan time, an Ex-vivo experiment of a mouse brain was conducted for this study. Using FSL, a tool for analyzing tensor images, we proposed a semi-automated segmentation and tractography analysis pipeline of the mouse brain and applied it to various mouse models. Also, in order to determine the useful signal-to-noise ratio of the diffusion tensor image acquired for the tractography analysis, images with various excitation numbers were compared. 자기공명영상(Magnetic Resonance Image)을 이용한 구조적 연구 방법에서 뇌 구조 세분화 방법은 최근 빠르게 발전하여 구조 이미지의 자동 분할을 위한 유능한 방법론이 되었다. 특히 아틀라스 정보를 이미지에 등록해 피사체의 이미지로 전달하는 분할(Segmentation) 방법은 아틀라스(Atlas)의 정확도에 편향되기 때문에 높은 정확도를 갖고 있는 아틀라스가 필요하게 된다. 알렌 마우스 뇌 아틀라스(Allen Mouse Brain Atlas)는 마우스의 아틀라스 중에서 높은 정확도를 갖고 있어 다양한 분야에서 사용되고 있으며, 신경섬유지도(Tractography)에 필수적인 마우스 뇌구조의 정확한 좌표와 분할 정보를 제공할 수 있다. 또한 기능적 연구 방법인 뇌의 백질 경로를 재구성하는 확산텐서영상(Diffusion Tensor Image)에 대한 확률론적 신경섬유지도를 사용하여 포괄적인 뉴런 네트워크를 매핑 하였다. 인간의 뇌 연구 결과와 마우스의 뇌 연구 결과는 비교분석 할 수 있어 인간에게 적용하기 어려운 실험들을 질환이 모델링된 마우스를 통해 결과를 얻어 임상적으로 이용이 가능하기 때문에 마우스 실험의 중요성이 올라가고 있다. 하지만 마우스를 이용한 연구에서 인간과 마우스의 뇌 크기 차이로 인한 문제가 있어 동등한 영상의 질을 달성하려면 다양한 조건이 필요하게 되며, 그중 대표적으로 충분히 긴 스캔시간이 필요하게 된다. 충분히 긴 스캔시간을 확보하기 위해 본 연구에서는 마우스의 뇌를 샘플화시켜 Ex-vivo 실험이 진행되었으며, 마우스 커넥톰(Connectome) 매핑에 대한 참조를 제공하기 위해 이 연구는 아틀라스 정규화 도구인 ANTx와 확산 텐서 영상을 분석할 도구인 FSL을 사용하여 마우스 뇌의 반자동 분할 및 신경섬유지도 분석 파이프라인을 제시하여 다양한 마우스 모델에 적용하고자 했다. 또한, 신경섬유지도 분석을 위해 획득하는 확산텐서영상의 유용한 신호대 잡음비를 결정하기 위해 다양한 여기수의 영상을 획득해 비교분석하였다.